W.T. Shaver memoirs - Shaver, W. T.
Memoirs relating to the service of the 12th Missouri Cavalry Regiment in the U.S. Army from 1864 to 1866. Describes Civil War skirmishes near Abbeville and Holly Springs, Miss., and battles at Franklin and Nashville, Tenn.
Typewritten transcript.
Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Army. -- Missouri Cavalry Regiment, 12th (1864-1866); Franklin, Battle of, Franklin, Tenn., 1864.; Nashville, Battle of, Nashville, Tenn., 1864.; Abbeville (Miss.); Holly Springs (Miss.); Mississippi -- History -- Civil War, 1861-1865.; Missouri -- History -- Civil War, 1861-1865.; Tennessee -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; Army officers